2022
DOI: 10.1016/j.jsps.2021.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the U.S. Post-marketing safety surveillance of COVID-19 vaccines

Abstract: Introduction Since December 2020, three COVID-19 vaccines have been authorized in the United States (U.S.) and were proceeded by large immunization programs. The aim of this study was to characterize the U.S. post-marketing safety (PMS) profiles of these vaccines with an in-depth analysis of mortality data. Methods This was a retrospective database analysis study. Details of the U.S. PMS reports (15 December 2020 to 19 March 2021) of the three vaccines (Pfizer-BioNTech,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…In this study, we found that the ORs of mRNA-1273 for severe AEs such as GBS, MT, DVT, and LP were significantly low compared to BNT162b2. The present study similarly found that the serious AEs of mRNA-1273 vaccination were slightly lower than BNT162b2 (49.0% versus 49.8%) [14]. On the other hand, Beatty A.L.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, we found that the ORs of mRNA-1273 for severe AEs such as GBS, MT, DVT, and LP were significantly low compared to BNT162b2. The present study similarly found that the serious AEs of mRNA-1273 vaccination were slightly lower than BNT162b2 (49.0% versus 49.8%) [14]. On the other hand, Beatty A.L.…”
Section: Discussionsupporting
confidence: 76%
“…We found that the reactogenicity in the PID cohort was overall lower than that of clinical trials data and from early post-authorization monitoring studies [19,20], similar or reduced to that reported in observational or real-world studies after two doses [14,21], and comparable or slightly reduced after boosters as well [22][23][24].…”
Section: Discussionsupporting
confidence: 61%
“…In total, 419 records were excluded after screening the title/abstracts. After assessing the 93 articles for eligibility, 2 studies evaluated complications for non‐mRNA vaccines, 14,15 7 discussed non‐cardiac complications, 16–22 14 studies were not case report/case series, 8,23–35 one study did not provide sufficient data 36 and these were therefore excluded. Finally, 69 articles met the eligibility criteria and were included in the present systematic review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%